Case study approach in post-occupancy evaluation research - Ratnasari, Anisza; Sudradjat, Iwan (ARTEKS : Jurnal Teknik Arsitektur, 2023)
A case study is a research approach that focuses on one or multiple real-life cases as the subject, encompassing both concrete entities such as individuals, groups, or organizations, as well as abstract constructs like processes, networks, or projects. This approach is employed to in-deep investigate complex issues and has been applied in various disciplines, such as; the social sciences, humanities, management, psychology, and architecture. The specific characteristics of a case study involve thorough exploration and analysis, data collection from diverse sources, and identification of key themes within the case. The strength of case studies lies in their ability to combine quantitative and qualitative data, enabling researchers to gain a profound understanding of the processes and outcomes of a phenomenon. This study applies a systematic literature review from several credible scholar articles. Two architectural case study researches are selected as precedents to provide a concrete overview of the characteristics, strengths, weaknesses, and procedural framework of implementing the case study approach. Analysis is conducted by comparing various gathered data to discern the potential for case studies to contribute to a comprehensive understanding of the complexity of issues and the quest for their solutions.